2020
DOI: 10.1093/mnras/staa1282
|View full text |Cite
|
Sign up to set email alerts
|

On the stellar kinematics and mass of the Virgo ultradiffuse galaxy VCC 1287

Abstract: Here, we present a kinematical analysis of the Virgo cluster ultradiffuse galaxy (UDG) VCC 1287 based on data taken with the Keck Cosmic Web Imager (KCWI). We confirm VCC 1287’s association both with the Virgo cluster and its globular cluster (GC) system, measuring a recessional velocity of 1116 ± 2 km s−1. We measure a stellar velocity dispersion (19 ± 6 km s−1) and infer both a dynamical mass ($1.11^{+0.81}_{-0.81} \times 10^{9} \ \mathrm{M_{\odot }}$) and mass-to-light ratio (M/L) ($13^{+11}_{-11}$) within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 79 publications
3
63
0
Order By: Relevance
“…The large population of UDGs in Coma and their survival in the cluster environment suggested large total masses, 𝑀 total , despite their modest stellar masses (van Dokkum et al 2015a). Further investigations and estimations of the total mass of UDGs using stellar kinematics (van Dokkum et al 2019;Chilingarian et al 2019;Müller et al 2020;Gannon et al 2020;Forbes et al 2021), globular clusters (GCs) dynamics Toloba et al 2018), H I kinematics (Trujillo et al 2017;Leisman et al 2017;Papastergis et al 2017;Mancera Piña et al 2020;Poulain et al 2021), weak ★ E-mail: teymur.saif@gmail.com gravitational lensing (Sifón et al 2018), UDG abundance in clusters (Amorisco 2018), scaling relations (Zaritsky 2017), and X-ray observations (Lee et al 2020) found that most UDGs are dark matter dominated objects with halo masses similar to those of dwarf galaxies and dynamical mass-to-light ratios that span a wide range between a few tens to a few thousands. The most massive known UDGs have 𝑀 total ∼ 10 11 𝑀 , comparable to the most massive dwarf galaxies, such as the LMC (Erkal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The large population of UDGs in Coma and their survival in the cluster environment suggested large total masses, 𝑀 total , despite their modest stellar masses (van Dokkum et al 2015a). Further investigations and estimations of the total mass of UDGs using stellar kinematics (van Dokkum et al 2019;Chilingarian et al 2019;Müller et al 2020;Gannon et al 2020;Forbes et al 2021), globular clusters (GCs) dynamics Toloba et al 2018), H I kinematics (Trujillo et al 2017;Leisman et al 2017;Papastergis et al 2017;Mancera Piña et al 2020;Poulain et al 2021), weak ★ E-mail: teymur.saif@gmail.com gravitational lensing (Sifón et al 2018), UDG abundance in clusters (Amorisco 2018), scaling relations (Zaritsky 2017), and X-ray observations (Lee et al 2020) found that most UDGs are dark matter dominated objects with halo masses similar to those of dwarf galaxies and dynamical mass-to-light ratios that span a wide range between a few tens to a few thousands. The most massive known UDGs have 𝑀 total ∼ 10 11 𝑀 , comparable to the most massive dwarf galaxies, such as the LMC (Erkal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mass measurements coming from stellar, and GC velocity dispersions, for many GC-rich UDGs confirm their dark matter dominated nature (van Dokkum et al 2016;Toloba et al 2018;van Dokkum et al 2019b;Martín-Navarro et al 2019;Forbes et al 2021;Gannon et al 2020Gannon et al , 2021. When used in comparison to a total halo mass estimate coming from GC numbers they can be used to infer basic halo properties (e.g., cusp vs. core) (Toloba et al 2018;Gannon et al 2020Gannon et al , 2021Forbes et al 2021).…”
Section: Introductionmentioning
confidence: 91%
“…The data were initially reduced using the KCWI data reduction pipeline (KDERP). Following this we took the non-sky subtracted, differential atmospheric refraction corrected and standard star calibrated 'ocubes' and performed the trimming and extra flat fielding steps described in Gannon et al (2020). Based on fits such as these we measure the recessional velocities and velocity dispersions as reported in Table 2.…”
Section: Kcwi Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations